Transformative Curriculum: Concepts, Implementation, and Challenges in History Education - Firmansyah, Haris; Atmaja, Thomi Sastra (FKIP Universitas Lampung, 2025)
Transformative Curriculum: Concepts, Implementation, and Challenges in History Education. Objectives: This study is designed to investigate the Transformative Curriculum's concept and implementation in the field of history education, as well as to pinpoint the obstacles that teachers and students face when implementing it in secondary schools. This research offers a comprehensive analysis of the Indonesian secondary education system's interpretation, practice, and challenge of Transformative Curriculum, unlike previous studies that primarily concentrated on curriculum theory or case studies in Western contexts. It emphasizes the local pedagogical, cultural, and policy-related dynamics that influence its implementation. Method: A qualitative approach with a phenomenological design was employed. Data were collected through in-depth interviews with teachers and students, classroom observations in history lessons, and document analysis. Findings: The results suggest that the Transformative Curriculum's implementation fosters students' reflective thinking, the development of empathy and awareness of social issues, and the connection between historical events and contemporary social contexts. Nevertheless, its implementation is impeded by a variety of challenges, such as inadequate learning resources, inadequate teacher training, and a curriculum structure that continues to prioritize rote memorization.. Conclusion: The Transformative Curriculum has the potential to significantly improve the critical and contextual comprehension of history among students. This study contributes to the literature by demonstrating the interaction between transformative learning theory and Indonesian cultural norms (e.g., reverence for authority, exam-oriented education) and by providing context-sensitive strategies for cultivating reflective historical thinking. Consequently, in order to optimize its implementation, educational policies should provide support for the continuous development of critical reflection-based learning resources and teacher training. Keywords: transformative curriculum, history education, critical thinking, social awareness, reflective learning.